Enhancing pesantren economy: Sharia-based cooperative training at Nurul Wafa Islamic Boarding School, Situbondo - Muhammad, Nur (Community Empowerment, 2025)
Community service activities focused on Sharia-based cooperative management and financial literacy training are crucial for strengthening the economy of pesantren, specifically at Pondok Nurul Wafa. This initiative aims to provide pesantren administrators and students with a comprehensive understanding of Sharia-based cooperative management and financial principles, while also encouraging the adoption of economic practices rooted in Islamic values. The training primarily focuses on transferring knowledge and skills related to Sharia-based cooperative management and finance to the participants. Through a series of comprehensive modules and interactive delivery methods, participants gain an in-depth understanding of Sharia management principles, financial analysis, strategies, and the implementation of Sharia-based cooperatives. The outcomes of this program include a significant improvement in participants' understanding of Sharia management, financial analysis, strategies, and the implementation of Sharia-based cooperative development. This program is expected to contribute to the enhanced economic well-being of the pesantren and its surrounding community.